2012
DOI: 10.3109/10837450.2012.723721
|View full text |Cite
|
Sign up to set email alerts
|

Applying response surface methodology to optimize nimesulide permeation from topical formulation

Abstract: Nimesulide is a non-steroidal anti-inflammatory drug that acts through selective inhibition of COX-2 enzyme. Poor bioavailability of this drug may leads to local toxicity at the site of aggregation and hinders reaching desired therapeutic effects. This study aimed at formulating and optimizing topically applied lotions of nimesulide using an experimental design approach, namely response surface methodology. The formulated lotions were evaluated for pH, viscosity, spreadability, homogeneity and in vitro permeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Number of thiol contents per gram of the TARX were determined by the quantification of thiol substituents using the Ellman’s reagent method [20, 21]. 0.5%, w/v dispersions of ARX (control) and TARX (sample) were prepared and diluted with 0.5 M phosphate buffer of pH 8.0 to a concentration of 0.15% w/v.…”
Section: Methodsmentioning
confidence: 99%
“…Number of thiol contents per gram of the TARX were determined by the quantification of thiol substituents using the Ellman’s reagent method [20, 21]. 0.5%, w/v dispersions of ARX (control) and TARX (sample) were prepared and diluted with 0.5 M phosphate buffer of pH 8.0 to a concentration of 0.15% w/v.…”
Section: Methodsmentioning
confidence: 99%
“…PG and SLS were used as permeation enhancer as per protocol of “Response Surface Methodology” (as enlisted in Table 2). This methodology was deployed to optimize topical formulations 19. These formulations were tested against full range of parameters, for instance, pH, temperature stability tests in 8°C±0.1°C, 25°C±0.1°C and 40°C±0.1°C and physical properties such as color, bleeding (separation of liquid) and rheology.…”
Section: Methodsmentioning
confidence: 99%
“…The mathematical form of the MLRA model is given as [9,25,26] where, β 0 , the intercept (demonstrating the mathematical mean of all numerical outcomes of 13 trials), β 1 and β 2 were the coefficients (calculated from the observed experimental values of Y), and X 1 and X 2 were coded levels of the independent variable(s). Polynomial equation, including interaction and quadratic factors were studied for all the response variables using the multiple linear regression analysis (MLRA) approach.…”
Section: Optimization Data Analysis and Numerical Optimizationmentioning
confidence: 99%